IMPLEMENTASI FINANCIAL TECHNOLOGY (FINTECH) PADA DEPOSITO DIGITAL BANK NEO COMMERCE (NEOBANK) - Yanty Faradillah Siahaan; Uci Ayuningrum; Lukman; Muhammad Raihan Auditya; Salsabila (P3M STMIK Profesional Makassar, 2026)
Financial Technology (FinTech) transformation has driven a shift in public investment behavior toward digital banking services offering efficiency and transparency. This study aims to analyze the profitability of digital deposit services at Bank Neo Commerce (NeoBank) and map optimal investment strategies for customers. The research employs a quantitative descriptive approach with Time Value of Money (TVM) calculation simulations based on fixed returns across various time intervals. The results indicate that NeoBank's digital deposit system accumulates profits precisely from yearly to hourly intervals, providing more measurable yield certainty compared to conventional banking. Decision Tree analysis recommends this product for investors with conservative to moderate risk profiles who prioritize liquidity and LPS security guarantees. This study concludes that FinTech implementation in digital deposits offers a balance between accessibility, security, and profitability.